2019
DOI: 10.1136/neurintsurg-2019-015171
|View full text |Cite
|
Sign up to set email alerts
|

Using G-FAST to recognize emergent large vessel occlusion: a training program for a prehospital bypass strategy

Abstract: IntroductionThe shorter the time between the onset of symptoms and reperfusion using endovascular thrombectomy, the better the functional outcome of patients. A training program was designed for emergency medical technicians (EMTs) to learn the gaze-face-arm-speech-time test (G-FAST) score for initiating a prehospital bypass strategy in an urban city. This study aimed to evaluate the effect of the training program on EMTs.MethodsAll EMTs in the city were invited to join the training program. The program consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Our experience is consistent with the reports from other medical systems that have implemented stroke alert systems to reduce door-to-needle time. [10][11][12] Notably, the present study demonstrated that the door-to-groin puncture time for thrombectomy candidates was also markedly reduced by pre-arrival notification, enabling the majority of patients to undergo groin puncture within 120 minutes. This is likely due to the longer time required to coordinate the neurointerventionist, interventional suite, and anaesthesiology care team; this process was initiated early with pre-arrival stroke notification.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our experience is consistent with the reports from other medical systems that have implemented stroke alert systems to reduce door-to-needle time. [10][11][12] Notably, the present study demonstrated that the door-to-groin puncture time for thrombectomy candidates was also markedly reduced by pre-arrival notification, enabling the majority of patients to undergo groin puncture within 120 minutes. This is likely due to the longer time required to coordinate the neurointerventionist, interventional suite, and anaesthesiology care team; this process was initiated early with pre-arrival stroke notification.…”
Section: Discussionmentioning
confidence: 60%
“…3 Future efforts should focus on pre-hospital screening of thrombectomyeligible patients with large vessel occlusion and establishment of a diversion system to ensure patients are transported to thrombectomy-capable hospitals. 10 One concern related to pre-hospital stroke screening was the potential for over-calling and thus overloading the acute stroke treatment pathway, thereby negatively affecting the AED service for patients with non-stroke emergencies. To maximise cost-effectiveness, the screening criteria were tailored to reduce notification for patients with stroke mimics and to exclude patients who were unlikely to benefit from acute reperfusion therapy.…”
Section: Discussionmentioning
confidence: 99%